The Evolving Role of Bariatric Surgery in Children and Adolescents Amid the Rise of GLP-1 Receptor Agonists: A Narrative Review - Jabłońska, Joanna; Wasik, Joanna; Armuła, Marta; Bongage, Claire; Piechowiak, Arkadiusz; Napieraj, Filip; Herc, Bartosz Przemysław; Tesla, Małgorzata; Gąska, Anna Agnieszka; Gutkowska, Marta (Quality in Sport, 2026)
Background. Pediatric obesity is a chronic, progressive disease associated with metabolic, cardiovascular, orthopedic and psychosocial complications. Metabolic and bariatric surgery can provide substantial and durable weight reduction in adolescents with severe obesity, but it is invasive and requires lifelong follow-up. The growing availability of glucagon-like peptide-1 receptor agonists may influence the role of surgery. Aim. This narrative review summarizes evidence on the indications, outcomes and complications of bariatric surgery in children and adolescents and discusses its evolving role in the era of GLP-1 receptor agonist therapy. Material and methods. PubMed, Scopus and Web of Science were searched for articles published between 2016 and 2026. Landmark studies and guidelines published before 2016 were also included. The search covered pediatric obesity, adolescent bariatric surgery, sleeve gastrectomy, Roux-en-Y gastric bypass, complications, type 2 diabetes, liraglutide, semaglutide and GLP-1 receptor agonists. Results. Metabolic and bariatric surgery provides the most established long-term evidence for substantial weight loss and improvement of obesity-related complications in adolescents with severe obesity. Liraglutide and semaglutide produce clinically meaningful short-term BMI reductions and may serve as alternatives or components of multimodal care. Surgery is also associated with improved mobility, physical function, musculoskeletal pain and health-related quality of life, whereas evidence on objectively measured fitness, participation in sport and routine perioperative use of GLP-1 receptor agonists remains limited. Conclusions. GLP-1 receptor agonists do not eliminate the need for metabolic and bariatric surgery in pediatric patients but may change treatment sequencing and shared decision-making. Care should be individualized, multidisciplinary and guided by effectiveness, psychological well-being and long-term safety.